Star formation in ‘the Brick’: ALMA reveals an active protocluster in the Galactic centre cloud G0.253+0.016 - Walker, Daniel Lewis; Longmore, Steven N.; Bally, John; Ginsburg, Adam; Kruijssen, Diederik; Zhang, Qizhou; Henshaw, Jonathan D.; Lu, Xing; Alves, João; Barnes, Ashley T.; Battersby, Cara; Beuther, Henrik; et al. (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. G0.253+0.016, aka ‘the Brick’, is one of the most massive (>105 M⊙) and dense (>104 cm−3) molecular clouds in the Milky Way’s Central Molecular